dep1 improves rice grain yield and nitrogen use efficiency simultaneously by enhancing nitrogen and dry matter translocation - Li-ying HUANG; Xiao-xiao LI; Yun-bo ZHANG; Shah FAHAD; Fei WANG (Journal of Integrative Agriculture, 2022)
The rice cultivars carrying dep1 (denseanderectpanicle1) have the potential to achieve both high grain yield and high nitrogen use efficiency (NUE). However, few studies have focused on the agronomic and physiological performance of those cultivars associated with high yield and high NUE under field conditions. Therefore, we evaluated the yield performance and NUE of two near-isogenic lines (NILs) carrying DEP1 (NIL-DEP1) and dep1-1 (NIL-dep1) genes under the Nanjing 6 background at 0 and 120 kg N ha−1. Grain yield and NUE for grain production (NUEg) were 25.5 and 21.9% higher in NIL-dep1 compared to NIL-DEP1 averaged across N treatments and planting years, respectively. The yield advantage of NIL-dep1 over NIL-DEP1 was mainly due to larger sink size (i.e., higher total spikelet number), grain-filling percentage, total dry matter production, and harvest index. N utilization rather than N uptake contributed to the high yield of NIL-dep1. Significantly higher NUEg in NIL-dep1 was associated with higher N and dry matter translocation efficiency, lower leaf and stem N concentration at maturity, and higher glutamine synthetase (GS) activity in leaves. In conclusion, dep1 improved grain yield and NUE by increasing N and dry matter transport due to higher leaf GS activity under field conditions during the grain-filling period.